Environmental management in Natura 2000 sites: Case study ; Baila county - Elisabeta Roşu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Biodiversity is a huge variety of ecosystems, species and genes, which represent the natural capital. The biodiversity values make up the natural heritage that must be used by the present generations without jeopardizing the chance of the next generations to enjoy the same living conditions. The protected natural areas represent the most important method to preserve biodiversity and to provide development patterns in harmony with nature, in the context of the fast economic development in the last decades. Natura 2000 represents a protected areas network, designated at from European level. Its aim is the preservation of the wild habitats and of endangered vegetal and animal species, as the proper management of these areas.
Keywords: 330; biodiversity; Natura 2000 sites; management